Report on five species of harpacticoid copepods from vegetative area of Sungai Pulai Johor - Kassim, Zaleha; Hasnan, Hazwani Hanim; Zainal, Syazleen; Ahmad Ishak, Nurul Huda (2017)
Bottom vegetation is known as preferred habitat for many types of meiofauna such as copepods. The conditions of sea bottom that include vegetation could contribute to the copepod’s assemblage. Being an important diet for fish larvae, information on copepod species promotes effort for conservation of both fish species and marine ecosystem. Nonetheless, identification and taxonomic report on copepods from such areas are still scanty. Samples of copepods were collected by scrapping the uppermost 10cm of sediment of bottom area at Sungai Pulai’s seagrass-bed during low tide. Sediment was decanted to extract the copepods which later be preserved in 5% buffered formalin. Body parts were dissected under microscope and prepared for taxonomic study. All drawings made with the help of Lucida tube were used for comparison with established key of identification. Five families were noted in this study; Ameridae Monard, Lang, Parastenhelia Thompson & A. Scott, Dactylopusiidae Lang, Tisbidae Sars and Diosaccidae Sars. Harpacticoid copepod species described from this study were Ameira sp. (Ameridae Monard, Lang), Parastenhelia sp. (Parastenhelia Thompson & A. Scott), Paradactylopodia sp. (Dactylopusiidae, Lang), Idyanthepusilla (Tisbidae, Sars) and Stenhelia sp. (Diosaccidae Sars). Further study on functional morphology would explain their adaptability to both conditions of sea bottom.